The Actin Cytoskeleton: A Mechanical Intermediate for Signal Integration at the Immunological Synapse - Roy, Nathan H.; Burkhardt, Janis K. (Frontiers in Cell and Developmental Biology, 2018)
The immunological synapse (IS) is a specialized structure that serves as a platform for cell-cell communication between a T cell and an antigen-presenting cell (APC). Engagement of the T cell receptor (TCR) with cognate peptide-MHC complexes on the APC activates the T cell and instructs its differentiation. Proper T cell activation also requires engagement of additional receptor-ligand pairs, which promote sustained adhesion and deliver costimulatory signals. These events are orchestrated by T cell actin dynamics, which organize IS components and facilitate their signaling. The actin network flows from the edge of the cell inward, driving the centralization of TCR microclusters and providing the force to activate the integrin LFA-1. We recently showed that engagement of LFA-1 slows actin flow, and that this affects TCR signaling. This study highlights the physical nature of the IS, and contributes to a growing appreciation in the field that mechanosensing and mechanotransduction are essential for IS function. Additionally, it is becoming clear that there are multiple types of actin structures at the IS that promote signaling in distinct ways. How the different actin structures contribute to force production and mechanotransduction is just beginning to be explored. In this Perspective, we will feature recent work from our lab and others, that collectively points toward a model in which actin dynamics drive mechanical signaling and receptor crosstalk during T cell activation.